Advances in Reflexive Sociology: Theory, Agency and Dialogical Inquiry - Tsekeris, Charalambos (Italian Sociological Review, 2012)
This theoretical essay seeks to comprehensively present and critically discuss the major advances in reflexive sociology, overtly promoting a kind of dialogical reflexivity. This mode of reflexivity claims to efficiently renounce the allegedly irreconcilable opposition between theory and agency, as well as to self-consciously challenge the frequent sociological dismissal of explanation and empirical reference. Hence, reflexive sociology ceases to be a monologic exhibition of epistemological power and tends to develop a more critical and collaborative character within the relational complexity of our contemporary social world.